Teachers’ Perception of the Implementation of Emancipated Curriculum at An Islamic High School in Parepare - Irwan, Zahrah Rafidah; Sakkir, Geminastiti; Asriati, Asriati (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This thesis aimed to find out the teachers’ perception of the implementation of the Emancipated Curriculum at an Islamic High School in Parepare. This research design used qualitative methods. The subject of the research was teachers in MAN 2 Kota Parepare in the academic year of 2024/2025. The sample are P5 supervisory team and English teachers. The data were collected by observation, interview and documentation. The researcher found that the Emancipated Curriculum at MAN 2 Kota Parepare is done well by teachers through planning, teaching, and checking on their teaching. The majority of teachers at MAN 2 Kota Parepare have positive opinions of the Emancipated Curriculum, which helps students become more engaged, think more clearly, and develop their knowledge and abilities. They believe it allows them greater flexibility to adapt their instruction to the needs of their students. Even while there are still certain difficulties, it also enhances learning using technology and encourages students to be more creative. All things considered; the introduction of the Emancipated Curriculum improves the learning environment. Teachers and students have more freedom with this curriculum.